PENGARUH KUALITAS PELAYANAN AKADEMIK DAN PROMOSI TERHADAP MINAT SISWA BARU DI MADRASAH - Zahrotul Azkiyah; Ari Kartiko; Muhammad Mujtaba Mitra Zuana (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2020)
In the world of education, many private schools have sprung up which will result in competition between schools in obtaining students. It can be seen that fostering new student interest in a school can be carried out by improving the academic services provided by the international standard madrasah, Amanatul Ummah, promotion by international standard madrasah community relations, Amanatul Ummah. Mojokerto, and which one has more influence on the quality of academic services and promotion on the interest of new students at MBI Amanatul ummah pacet Mojokerto. This study uses quantitative data analysis techniques. Types of data collection using a questionnaire, test instruments using validity and reliability tests. classical assumption test and hypothesis testing using simple linear regression test and multiple linear regression. The results of this study indicate that the results of data analysis using the F test and t test obtained significant simultaneous test data (F test) of 0.000 and an F coefficient value greater than the F value (F count = 47.863> F 0.1 = 2.37 ). This means that there is a significant positive effect on the quality of academic services and promotion on the interest of new students at MBI Pacet Mojokerto. The greatest relationship to variable Y (new student interest) is shown by variable X2 (promotion), namely 0.514 or 51.4%.